(untitled) (Journal of Pharma Insights and Research, 2026)
Chronic wound management is a significant clinical hurdle due to the persistent inflammatory state, localized hypoxia, and microbial colonization that characterize non-healing ulcers. Conventional treatments frequently fail to address the complex biochemical environment of diabetic and pressure-induced wounds. Herbal-integrated hydrogels represent a sophisticated intersection of material science and pharmacology, utilizing the intrinsic biocompatibility of cross-linked polymers alongside the therapeutic diversity of plant-derived secondary metabolites. These systems facilitate a moist wound environment while enabling the sustained release of bioactive compounds such as flavonoids, terpenoids, and alkaloids. These biomaterials address the root causes of healing arrest by modulating the oxidative stress within the wound bed and promoting the transition of macrophages from the pro-inflammatory M1 to the pro-healing M2 phenotype. Advanced formulations incorporating natural gums and polyphenolic extracts show superior efficacy in stimulating neovascularization through the upregulation of pro-angiogenic markers like CD31 and alpha-smooth muscle actin. The inherent antimicrobial properties of specific phytochemicals provide a non-antibiotic strategy to disrupt bacterial biofilms, mitigating the risks associated with multi-drug-resistant pathogens. The synergy between the hydrogel matrix and encapsulated phytoconstituents optimizes epithelialization and collagen deposition, ultimately restoring tissue integrity. These cost-effective and safe biomimetic platforms offer a viable alternative to synthetic dressings, promising improved patient outcomes in the treatment of refractory cutaneous lesions and chronic skin injuries